Execution of the Tasks of Geotourism in the Post-Mining Objects and Sites as the Way for Using and Promoting Former Industrial and Mining Facilities - Kobylańska, Malwina; Lorenc, Marek W. (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2019)
Each geotourist venture should be related to the creation of a tourist product from the geological or post-mining object. This preparation to tourist traffic through the adaptation or making the object available to visitors is the primary objective which implies the series of different tasks. These tasks of geotourism, in post-mining objects and sites - the special type of cultural heritage resources, are presented in the paper. Execution of each task was discussed on the basis of different examples of development of post-exploitation sites all over the world, e.g. in Spain, Poland, Germany, England, and Australia. The form and scope of the geotourist tasks execution formed the base for the authors for the assessment of selected development practices, as well as the definition of application guidelines introduced in this paper. All tasks facing geotourism based on former industrial and mining facilities should form a coherent whole, covering the economic (profitability), ecological (neutrality) and socio-cultural aspect (social justice), and thus fit in the concept of sustainable development in tourism. These pillars should be treated equally, because only their reasonable combination has the chance to result in the creation and development of sustainable tourism.